Does corporate governance reform necessarily boost firm performance? Recent evidence from Russia - Mihails Kuznecovs; Sarmistha Pal (Institute for the Study of Labor (IZA), 2012)
This paper examines whether the introduction of corporate governance (CG) reforms in general and that of transparency and disclosure (T&D) rules in particular can necessarily boost firm performance. Existing literature suggests that CG reforms can boost performance because it can resolve the conflict of interest between the controlling and the minority owners, especially in societies with highly skewed distribution of ownership. We however argue that the success of CG reform would, in addition, depend on whether the reforms may initiate further conflict, e.g., that between the state and the controlling owners. Using recent data from Russia for 2000-2008, we find that the introduction of corporate governance codes in Russia had limited success to improve indices of firm performance in our sample. We argue that this arises from the predatory behavior of the central and local governments: greater transparency make businesses easy targets for aggressive tax enforcement policy by the central government while the decentralized local governments may increase the bribe price to protect businesses from high central taxes, which may also induce some businesses to go underground, thus harming firm performance.
urn:nbn:de:101:1-201208096371
Keywords: G3; K2; P2; 330; corporate governance reform; transparency and disclosure rules; conflict between state and the controlling owner; taxation and fiscal decentralisation; firm performance; predatory state; Tobin's Q; Russia; Corporate Governance; Reform; Unternehmenserfolg; Staatliche Einflussnahme; Übergangswirtschaft; Russland